2014
DOI: 10.1177/1040638714523773
|View full text |Cite
|
Sign up to set email alerts
|

DisseminatedBlastomyces dermatitidis, genetic group 2, infection in an alpaca (Vicugna pacos)

Abstract: A 7-year-old, female Huacaya alpaca presented with a 3-week history of left-sided head tilt and mild ataxia. Despite aggressive supportive therapy with empirical antibiotic, anti-inflammatory, thiamine, and anthelminthic therapy, neurologic signs progressed to a right-sided head tilt, positional nystagmus, and episodes of severe ataxia and obtundation. On necropsy, discrete expansile to poorly delineated infiltrative masses with tan, creamy to grumous exudate were observed in the right petrous temporal bone, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…In this case, a deep C2 ulcer was revealed on postmortem examination, which may have contributed to the patient's morbidity. While a similar clinical case of disseminated blastomycosis in an alpaca was recently reported, to our knowledge, this is the first report of microforms found in this or any veterinary species …”
Section: Discussionsupporting
confidence: 71%
“…In this case, a deep C2 ulcer was revealed on postmortem examination, which may have contributed to the patient's morbidity. While a similar clinical case of disseminated blastomycosis in an alpaca was recently reported, to our knowledge, this is the first report of microforms found in this or any veterinary species …”
Section: Discussionsupporting
confidence: 71%
“…1,16 Of the differentials at autopsy (each of which have been recognized in other species at this locale), the paucity of reports regarding the occurrence of cryptococcosis, histoplasmosis, aspergillosis, rhodococcosis, and blastomycosis in camelids, specifically llamas, made these diseases less likely than tuberculosis. 4,[10][11][12]15,23 B. dermatitidis was identified microscopically and confirmed via DNA sequencing, and there was no evidence of mycobacterial infection.…”
mentioning
confidence: 99%
“…A 2014 report of disseminated blastomycosis in an alpaca raised the issue of genetic subgroups within the Blastomyces genus and called for active surveillance to expand the knowledge of the genetic and geographic diversity of this pathogen. 12 In addition, differentiation from Blastomyces gilchristii , which was identified in 2013 in a limited geographic range (Wisconsin, Minnesota, and Ontario) but associated with acute respiratory syndrome, was considered critical. 5,7 In order to more completely define the organism in this case, we pursued DNA sequencing.…”
mentioning
confidence: 99%
“…In that study, 46 nucleotide polymorphisms were identified within 7 gene regions, with 12 SNPs being determined as diagnostic between B. gilchristii and B. dermatitidis . Genotyping of a small number of isolates by both methods indicates that B. gilchristii , the newly proposed species, may be equivalent to microsatellite genetic Group 1 with B. dermatitidis being equivalent to microsatellite genetic Gr 2 [ 7 , 8 ]. This suggests that clinical disease variation is potentially associated with species-specific genetic diversity.…”
Section: Introductionmentioning
confidence: 99%